Formulation Development and Evaluation of Mouth Dissolving Tablets of Loratadine - Kabir, Abu Kalam Lutful; Rahman, Shaikh Mukidur; Jahan, Md Arshad; Rouf, Abu Shara Shamsur (Stamford Journal of Pharmaceutical Sciences, 2010)
Difficulty in swallowing (dysphagia) is common among all age groups, especially in elderly and pediatrics. Mouth dissolving tablets constitute an innovative dosage forms that overcome the problems of swallowing and provides a quick onset of action. The purpose of this study was to formulate and evaluate mouth dissolving tablet of loratadine using a special preparation technology (pharmaburst Technology) with a super disintegrating agent (Croscarmellose sodium). Tablets were prepared by direct compression technique. The granules were evaluated for angle of repose, bulk density, tapped density, bulkiness, compressibility index and hausners ratio. The tablets were evaluated for hardness, thickness, uniformity of weight, friability, wetting time, water absorption ratio, disintegration time and drug content. In vitro release studies were performed using USP-II (paddle method) in 900ml of pH 1.2 at 50rpm. The physical properties of the prepared tablets did not show any significant variations and were found to have good physical integrity. Tablets prepared with pharmaburst B2 and Croscarmellose sodium showed a lesser disintegration time and wetting time of 27±0.10 and 38±0.13 seconds respectively. The best formulations were subjected to stability studies at 40ºC/75% RH for 60 days. Key words: Loratadine; pharmaburst B2; croscarmellose sodium; mouth dissolving tablets; direct compression. DOI: 10.3329/sjps.v2i2.5825 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 59-65